Generation and validation of a novel multitarget small molecule in glioblastoma - Aizpea Artetxe-Zurutuza; Nerea Iturrioz-Rodriguez; Joseba Elizazu; Mireia Toledano-Pinedo; Alicia Porro-Pérez; Irati De Goñi; Alejandro Elua-Pinin; Linda Schäker-Hübner; Mikel Azkargorta; Felix Elortza; Isabel Iriepa; Francisco Lòpez-Muñoz; et al. (Cell Death and Disease)
Abstract The development of multitarget small molecules (MSMs) has emerged as a powerful strategy for the treatment of multifactorial diseases such as cancer. Glioblastoma is the most prevalent and malignant primary brain tumor in adults, which is characterized by poor prognosis and a high heterogeneity. Current standards of treatment present limited effectiveness, as patients develop therapy resistance and recur. In this work, we synthesized and characterized a novel multi-target molecule (named DDI199 or contilistat), which is a polyfunctionalized indole derivative developed by juxtaposing selected pharmacophoric moieties of the parent compounds Contilisant and Vorinostat (SAHA) to act as multifunctional ligands that inhibit histone deacetylases (HDACs), monoamine oxidases (MAOs) and cholinesterases (ChEs), and modulate histamine H3 (H3R) and Sigma 1 Receptor (S1R) receptors. DDI199 exerts high cytotoxic activity in conventional glioblastoma cell lines and patient-derived glioma stem cells in vitro. Importantly, it significantly reduces tumor growth in vivo, both alone and in combination with temozolomide (TMZ). The comparison with SAHA showed higher target specificity and antitumor activity of the new molecule. Transcriptomic and proteomic analyses of patient-derived glioma stem cells revealed a deregulation in cell cycle, DNA remodeling and neurotransmission activity by the treatment with DDI199. In conclusion, our data reveal the efficacy of a novel MSM in glioblastoma pre-clinical setting.